2020
DOI: 10.1186/s40249-020-00640-3
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for simulating the phase-based transmissibility of a novel coronavirus

Abstract: Background: As reported by the World Health Organization, a novel coronavirus (2019-nCoV) was identified as the causative virus of Wuhan pneumonia of unknown etiology by Chinese authorities on 7 January, 2020. The virus was named as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by International Committee on Taxonomy of Viruses on 11 February, 2020. This study aimed to develop a mathematical model for calculating the transmissibility of the virus. Methods: In this study, we developed a Bats-Hosts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
714
5
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 762 publications
(770 citation statements)
references
References 28 publications
16
714
5
11
Order By: Relevance
“…In the second week the working time reduced and effective reproduction number decreased to 4.29 from 13 th day to 16 th . Comparing to the other researches, the results showed that R of COVID-19 in Iran in the early stages were higher than the previous estimated basic reproduction number [1][2][8] [9][10] [11].…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In the second week the working time reduced and effective reproduction number decreased to 4.29 from 13 th day to 16 th . Comparing to the other researches, the results showed that R of COVID-19 in Iran in the early stages were higher than the previous estimated basic reproduction number [1][2][8] [9][10] [11].…”
Section: Discussioncontrasting
confidence: 71%
“…Previous studies estimated basic reproduction number between 2.2 and 4. Chen et.al [1] showed that the basic reproduction number of COVID-19 was 3.58 using the reported data in Wuhan City, China. Read et.al [8] showed that the ܴ of COVID-19 was between 3.6 and 4.…”
Section: Discussionmentioning
confidence: 99%
“…Besides hospitalized or confirmed cases, many asymptomatic individuals potentially carry the virus. Thus, diagnosing the patients and finding the asymptomatic carriers will help us understand the exact viral transmission routes.Simulation studies can mathematically modelthe contribution of the asymptomatic carriers in person-person viral transmission [4], highlighting thatfulminating cases are unlikely to be the only viral sources. Reportedly, the viral load in an asymptomatic carrier is akin to that in a symptomatic patient; thus, asymptomatic or minimally symptomatic patientsare likelyto transmit the virus as well as symptomatic patients.…”
Section: Dear Editormentioning
confidence: 99%
“…Their estimations based on likelihood and model analysis showed that R 0 with control measures might be as high as 6.47 ( [5]). Most recently, Chen et al ( [11]) developed a Bats-Hosts-Reservoir-People transmission network model to simulate the potential transmission from the infectious sources to human. The estimated values of R 0 were 2.30 from reservoir to person and 3.58 from person to person.…”
Section: Introductionmentioning
confidence: 99%